2023
DOI: 10.3390/bioengineering10020264
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Habitual Foot Strike Patterns on the Morphology and Mechanical Function of the Medial Gastrocnemius–Achilles Tendon Unit

Abstract: As a crucial and vulnerable component of the lower extremities, the medial gastrocnemius–Achilles tendon unit (gMTU) plays a significant role in sport performance and injury prevention during long-distance running. However, how habitual foot strike patterns influence the morphology of the gMTU remains unclear. Therefore, this study aimed to explore the effects of two main foot strike patterns on the morphological and mechanical characteristics of the gMTU. Long-distance male runners with habitual forefoot (FFS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…The study found that the normalized FL increased significantly in the GR group after training, and the FL of the MG increased significantly in both groups after training. A prior study has also provided evidence that long-term running with FFS could significantly influence the architecture of MG, resulting in runners having a longer FL ( Li et al, 2023 ). Compared with running with RFS, running with FFS requires more active involvement from the MG ( Lin et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The study found that the normalized FL increased significantly in the GR group after training, and the FL of the MG increased significantly in both groups after training. A prior study has also provided evidence that long-term running with FFS could significantly influence the architecture of MG, resulting in runners having a longer FL ( Li et al, 2023 ). Compared with running with RFS, running with FFS requires more active involvement from the MG ( Lin et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…The FL was defined as the length of the fascicular pathway between the superficial and deep fascias, and it was determined by calculating the average length of three fascicles in an ultrasound image ( Geremia et al, 2019 ). The normalized FL was obtained by dividing the FL by the shank length ( Li et al, 2023 ). The PA was defined as the angle formed between the muscle fascicle and deep fascia, the mean value of which was calculated according to the three ultrasound images of each participant ( Geremia et al, 2019 ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation